Agrarian Conflict in Indonesia: A Literature Review of The Relationship Between Hegemony and Ecological Impact - Dewicca Fatma Nadilla; Bambang Subiyakto; Rochgiyanti Rochgiyanti; Deasy Arisanty; Syaharuddin Syaharuddin (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
Agrarian conflict in Indonesia is a pressing structural issue, as it involves unequal access to land between the state, corporations, and indigenous communities. This study aims to examine the dynamics of agrarian conflict and state hegemony in controlling agrarian resources, while analyzing the resulting ecological impacts. The method used is a literature study with a descriptive qualitative approach, analyzing various legal documents, reports from civil society organizations, and academic and media articles. The results of the study indicate that the state, through national strategic projects and the granting of concessions such as HGU, often ignores the customary rights of local communities, triggering social conflict and damaging the ecological order. This form of domination is reinforced by the weak recognition of customary law and minimal public participation in the formulation of agrarian policies. Ecologically, agrarian conflict has an impact on deforestation, land degradation, environmental pollution, and a sustainability crisis. The study's conclusions confirm that the state exercises hegemony in agrarian conflict in Indonesia through coercive and ideological power, which legitimizes land grabbing in the name of development. Case studies show a pattern of land acquisition without community consent, which causes social conflict and ecological damage, and marginalizes the role of local communities in decision-making.